Effectiveness of Marketing Communications in Building Brand Image and Customer Loyalty - Pratiwa Dyatmika (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2024)
Marketing communications is an important part of building a strong brand image and high customer loyalty. The aim of this work is to investigate the effectiveness of marketing communications to achieve these objectives, using a qualitative approach that includes literature research, customer interviews and interviews with marketers. The research results show that effective, consistent and integrated marketing communications can help create positive brand perceptions and associations in customers, thereby encouraging a favorable brand image. Marketing communication elements such as loyalty programs, sales promotions and post-purchase communications are considered the most effective in maintaining customer loyalty. In addition, digital marketing communications, word-of-mouth (WOM) and electronic word-of-mouth (eWOM) have a significant influence on brand image and customer loyalty. Personalization and personalization of marketing communications are also considered important for message relevance, customer engagement, and strengthening brand relationships. However, this research also reveals that some customers doubt the credibility of marketing communications and there are customers who are not loyal because of their true loyalty. Overall, the results of this research highlight the importance of effective and integrated marketing communications tailored to customer preferences and behavior in building a positive brand image and increasing customer loyalty.